The narrative of the Caucasian schism: memory and forgetting in medieval Caucasia - Aleksidze, Nikoloz (Corpus scriptorum Christianorum orientalium, 2018)
In the early seventh century, the Georgian and the Armenian Churches separated. Since then, the two nations formed their distinct Christian cultures and national Churches. This also resulted in mutual antagonism, the repercussions of which are still observable in modern Caucasia. This is the prevalent narrative that one encounters in modern histories of medieval Caucasia. In the centre of this narrative lies the Schism, a watershed that divides the history of Caucasia into two chronological constituents, the era before and after. Indeed, the Schism is allegedly one of the most well documented events in Caucasian history, infinitely evoked and referred to in medieval Armenian historical accounts. The present study is an attempt to deconstruct this grand narrative by focusing on the formation of the narrative of the Schism, its central element. It argues that the narrative of the Schism was perpetually reconstructed and reinvented by medieval historians for the purpose of sustaining teleological continuity in their perception of the region's history. In the historical imaginaries of different medieval writers in different times and places, the Schism served as an interpretive tool in attempts to create a sound connection between the present and the forgotten past. The Schism was once again reinvented in contemporary Armenian and Georgia national discourses, and thence has made its way into scholarly studies